Diversity of culturable halophilic archaea isolated from Rambla Salada, Murcia (Spain). - Luque, Rocío; González-Doménech, Carmen María; Llamas, Inmaculada; Quesada, Emilia; Béjar, Victoria (Springer Nature, 2012)
We have studied the diversity of culturable halophilic Archaea at Rambla Salada, Murcia (south-eastern Spain). We made 8 samplings at different places in this habitat during the years 2006 and 2007 and isolated a total of 49 strains, which were identified by means of phenotypic tests and the hypervariable V1-V3 region of the 16S rRNA gene sequences (around 500 bp). The ribosomal data showed that the isolates belonged to 12 genera within the Halobacteriaceae family, with Haloferax and Natrinema being the most abundant. Five strains showed less than 97% sequence identity with validly described species and may well represent new taxa. All the strains grew best with around 25% w/v salts, required high concentrations of NaCl and magnesium and produced red to pink colonies. They were facultative anaerobes with both respiratory and fermentative metabolisms. The diversity of the archaeal community was analysed with the MOTHUR package. We identified 14 OTUs at the 3% genetic distance level and found quite high diversity. Rarefaction curves of richness estimators and diversity indices demonstrated that our collection of isolates represented the archaeal community at Rambla Salada that can be isolated under the conditions used in this work. This is the first report to be published on the culturable archaea at Rambla Salada, an area of considerable ecological interest.
Keywords: Microorganismos halófilos; Bacteriología - Cultivos y medios de cultivo; Diversity; MOTHUR; 16S rRNA; Culturable halophilic; Archaea